2013
DOI: 10.1080/20421338.2013.820449
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Contributions of an Indigenous Tree in Urban Areas of Southwest Nigeria

Abstract: Indigenous trees have been discovered to be disappearing from urban areas at alarming rates, and the contributions of the existing trees are not adequately documented. Milicia excelsa is an indigenous trees species in tropical Africa and popularly known as Iroko. Due to extensive exploitation for wood production and other socio-economic activities, the tree species is classified as threatened and relics could only be found in a few locations. A survey of the trees in the city of Ibadan was therefore carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Similarly, Shikur (2012) found exotic tree species to account for between 60 and 80% in Addis Ababa, Ethiopia while Seburanga et al (2014) found exotic species to account for 75% in urban settlements of Kigali, Rwanda. In Nigeria, Babalola et al (2013) and Agbelade et al (2017) reported more exotic than native species in Ibadan and the Federal Capital Territory, Abuja respectively. This implies an increasing dominance of exotic trees species in the continent hence, raising the fear of gross alterations in the abundances of native species and their exposure to increased risk of local extinction (Farmilo et al, 2014).…”
Section: Urban Trees and Forests Diversity In Africamentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Shikur (2012) found exotic tree species to account for between 60 and 80% in Addis Ababa, Ethiopia while Seburanga et al (2014) found exotic species to account for 75% in urban settlements of Kigali, Rwanda. In Nigeria, Babalola et al (2013) and Agbelade et al (2017) reported more exotic than native species in Ibadan and the Federal Capital Territory, Abuja respectively. This implies an increasing dominance of exotic trees species in the continent hence, raising the fear of gross alterations in the abundances of native species and their exposure to increased risk of local extinction (Farmilo et al, 2014).…”
Section: Urban Trees and Forests Diversity In Africamentioning
confidence: 99%
“…A number of studies in Nigeria (Agbelade et al, 2016a;Babalola et al, 2013) and South Africa (Sheona et al, 2015) have revealed that urban and peri-urban trees provide environmental/ecological values such as beautification, protection of houses and provision of shade, habitat for some birds, serving as phorophytes for orchids and other epiphytes and generally improving peoples' social interaction and children outdoor playing. They also have economic values such as being sources of food, nutrition supplement, fuelwood and animal fodder (Agbelade et al, 2017).…”
Section: Values Of Urban Trees and Forests In Africamentioning
confidence: 99%
See 2 more Smart Citations
“…For example, [16], used 1,200 copies of questionnaires in Ekiti State in Southwest Nigeria to look for reasons why people plant trees. Similarly, the study of [17] utilized semi-structured questionnaires to survey the trees in the city of Ibadan Southwest Nigeria and the people living close to the trees or working in the locations where the trees are sighted to determine the socioeconomic benefits. A total of 65 trees (0.14 trees/km 2 ) of M. excelsa were sighted.…”
Section: Introductionmentioning
confidence: 99%